THE STUDENTS’ PERCEPTION IN SPEAKING ENGLISH OF THE TENTH AT THE ISLAMIC BOARDING SCHOOL OF TUNAS HARAPAN TEMBILAHAN - Nana Herawati; Edi Ardian; Sri Erma Purwanti (Program Studi Pendidikan Bahasa Inggris, 2024)
The importance of conducting this research is to introduce students to the fact that learning speaking english can help students get used to speaking english. The researcher conducted this research to find out information about students’ perception of learning english speaking at the Islamic boarding school of tunas harapan tembilahan as an illustration of whether the implementation of learning english speaking can support students’english proficiency. The research design is quantitative descriptive. The population of this study were all students of class X which only consisted of 1 class, from the Islamic boarding school of tunas harapan tembilahan. To determine the sample, researchers used total sampling technique,, the total number of population is 20 students. In collecting data, researchers used a questionnaire as a research tool. This questionnaire was used to find out how the students’ perceptions of the implementation of learning english speaking at the Islamic boarding school of tunas harapan tembilahan. The questionnaire used in the study is presented in 5 ( five) alternatives commonly known as the likert scale. The results showed that the students’ perception of learning speaking english was good (70.2%). Because 70.2% lies between 66-100%. So, it can be said that the students’ perception of learnig speaking english at the Islamic boarding school of tunas harapan tembilahan is good.